2019
DOI: 10.1002/jcb.28974
|View full text |Cite
|
Sign up to set email alerts
|

EMP1 regulates cell proliferation, migration, and stemness in gliomas through PI3K‐AKT signaling and CD44

Abstract: Glioblastoma multiforme (GBM) is an intracranial tumor; the feature is higher malignant and poorer prognosis. The search for therapeutic targets for gliomas has always been a focus of research in the field of neurology. The unusual expression of epithelial membrane protein 1 (EMP1) has been proved in most tumors. In our study, we determined the expression level of EMP1 expression in glioma tissues. There were higher levels of EMP1 in glioma tissues—particularly GBM tissues—than those in normal brain tissues. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…11 Studies have shown that EMP1 plays a crucial part in cell adhesion, proliferation, apoptosis, differentiation, tumor formation and metastasis. 12,13 Li et al found that in glioblastoma, highly expressed EMP1 promotes tumor cell proliferation, invasion and metastasis by activating PI3K/AKT/mTOR signaling pathway. 14 Ogita et al found that EMP1 binding with copine-III promoted the expression of Src, Vav2 and Rac1 in prostate cancer, leading to enhanced migration and metastasis of prostate cancer cells, indicating that EMP1 may take a part in the positive regulation of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have shown that EMP1 plays a crucial part in cell adhesion, proliferation, apoptosis, differentiation, tumor formation and metastasis. 12,13 Li et al found that in glioblastoma, highly expressed EMP1 promotes tumor cell proliferation, invasion and metastasis by activating PI3K/AKT/mTOR signaling pathway. 14 Ogita et al found that EMP1 binding with copine-III promoted the expression of Src, Vav2 and Rac1 in prostate cancer, leading to enhanced migration and metastasis of prostate cancer cells, indicating that EMP1 may take a part in the positive regulation of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that EMP1 mediates PRD resistance induced by the interaction of leukemic cells with mesenchymal stem cells (16). EMP1 is upregulated in glioblastoma multiforme and its inhibition decreases proliferation and invasiveness of tumor (28)(29)(30). In contrast, in carcinoma of the nasopharynx, stomach, breast, urothelium, and prostate, EMP1 reduces cell migration and invasion and increases apoptosis and caspase-9 expression (27,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…EMP1 belongs to the peripheral myelin protein 22-kDa (PMP22) gene family. It promotes glioblastoma progression through the PI3K/AKT/mTOR signaling pathway 6 , and the unusual expression of EMP1 has been revealed in most tumor types 12 . TPM1 gene is a member of a tumor-associated protein family (the tropomyosin family) -it plays an important role in tumor-specific variations of actin filament aggregation via stress fiber modulation and actin cytoskeleton modification 7 .…”
Section: Discussionmentioning
confidence: 99%